Adapting reading tasks in the textbook English 12 to improve 12th form students’ reading achievement . M.A Thesis Linguistic: 60 14 10 - Vũ, Thị Thanh Huyền, 1985- (University of Languages and International Studies, 2017)
In learning a language, students show their different needs as well as different language proficiency. Therefore, materials adaptation can be considered as a very important step in language teaching and learning in general and teaching English reading skill in particular so students will understand the content of reading materials with less frustration.The study aims at investigating students’ opinions about reading tasks in the textbook English 12. Based on students’ opinions about reading tasks, the teacher attempts to find how to adapt them. Then the teacher applied those adapted tasks in teaching English in the classroom to help students of gr oup 12A1 of Kim Bang A high school have more chances to practice reading and improve their reading achievement. The results indicated that most of the adapted tasks were suitable to students and helped them improve reading achievement slightly. Briefly, the study suggests some adapted reading activities and tasks for teachers to utilize to increase the effectiveness of English reading lessons when applied to the textbook English 12 to teach the 12th form students at Kim Bang A high school.